Behavioral and Antinociceptive Effects of Alfentanil, Butorphanol, and Flunixin in Horses - Queiroz-Neto, Antonio; Zamur, Guilherme; Mataqueiro, Maria I.; D'Angelis, Flora H.F.; Araújo, Renatha A.; Silva, Matheus H.M.; Basile, Roberta C.; Ferraz, Guilherme C. (Elsevier, 2013)
To determine the behavioral and antinociceptive effects of narcotic and non-narcotic analgesics administered by intravenous injection in horses, 10 thoroughbred mares weighing between 450 and 550 kg and ranging in age from 8 to 13 years old were analyzed. The effects of alfentanil, butorphanol, flunixin, and saline solution on the general activity of the horses were investigated by measuring spontaneous locomotor activity (SLA) and head height (HH) in two behavior stalls. The antinociceptive effects of alfentanil (0.02 mg kg-1), butorphanol (0.1 mg kg-1), flunixin meglumine (0.5 mg kg-1), and saline were determined by measuring skin twitch reflex latency (STRL) after thermal cutaneous nociceptive stimulation. A paired Student t-test was used to compare SLA and HH between the groups of horses receiving different doses of the same drug at various time points. The Tukey test was used to compare the antinociceptive effect of the treatments. Differences were considered significant when P value was <.05. Horses treated with opioid analgesics demonstrated excitation, as shown by a significant increase in SLA at all doses tested and by neighing and demonstrating attentive attitudes with movement of the ears, stereotypical walking, and ataxia in most of the animals. HH was elevated only in animals treated with alfentanil. Antinociception was observed at 5 and 30 minutes after administration of alfentanil and butorphanol, respectively. Increased SLA was observed at 30 and 90 minutes after administration of alfentanil and butorphanol, respectively. We observed no effect on antinociception in horses given flunixin. In conclusion, this study suggests that alfentanil has a faster onset and a shorter duration than butorphanol; however, both drugs are able to stimulate the central nervous system. © 2013 Elsevier Inc. All rights reserved.
Keywords: Analgesics; Motor activity; Opioid